In-situ and sensitive stability study of emulsion and aluminum adjuvanted inactivated foot-and-mouth disease virus vaccine by differential scanning fluorimetry analysis. Issue 14 (23rd March 2020) - Song, Yanmin; Yang, Yanli; Lin, Xuan; Li, Xiunan; Zhang, Xuan; Ma, Guanghui; Su, Zhiguo; Zhang, Songping
Highlight: DSF was employed for in-situ analyses of iFMDV stability in different adjuvants. SYBR Green II enables sensitive detection of iFMDV as low as 5 μg/mL. Different adjuvants showed different destabilization or stabilization on iFMDV. Excipients were screened by DSF in adjuvants and were verified by HPSEC and DSC. DSF is also applicative for DNase treated iFMDV and pre-adjuvanted iFMDV vaccines. Abstract: Adjuvants are important to enhance the antigens immunogenicity, but may also alter the structures of antigens. Currently off-line methods for adjuvants induced antigen alteration suffer from incomplete release and possible structural alteration of antigens. Here we investigated the differential scanning fluorimetry (DSF) as an in-situ and high-throughput strategy to analyze the stability of inactivated foot-and-mouth disease virus (iFMDV), known as 146S, in three representative adjuvants including aluminum hydroxide (AH), oil-in-water (O/W) emulsion, and water-in-oil (W/O) emulsion. Under optimized DSF conditions, the T m referring to 146S dissociation can be detected in all three adjuvants. Using SYBR Green II as fluorescent dye enables detection of iFMDV as low as 5 μg/mL. By comparing the T m in different pH, three adjuvants showed different effects on 146S. Screening for excipients was successfully conducted using DSF. Sugars and glycerol increased the T m of iFMDV in all three adjuvants, but to different degree. The stabilization by 20% (w/v) sucrose and glycerol was further verified by differential scanning calorimetry (DSC) and high performance size exclusion chromatography (HPSEC). DSF is proved also applicative for low-purity iFMDV and pre-adjuvanted iFMDV vaccines. In summary, the DSF can be a powerful tool in formulation study and vaccine quality control for inactivated virus vaccines.